Memaknai Kekerasan Ilahi dalam Narasi Air Bah: Sebuah Kajian atas Kejadian 6:1-9:19 - Kornelius Andrian Roma Lumbanbatu (THRONOS: Jurnal Teologi Kristen, 2023)
Contemporary intellectuals often criticize the flood narrative (Gn. 6:1-9:19) due to the content of violence in it. In the face of these critiques, I argue for a position that perceives the violence of the flood narrative in a positive light. I defend this argument through a threefold explanation constructed by library research on three exegetical works highlighting the divine violence in the flood narrative—each written by Emanuel G. Singgih, Merilyn E. K. Clark, and Stephen M. Wilson, respectively. The first part contains a detailed exposition of the aforementioned works. The second part contains my analysis of these works based on Eric A. Seibert’s typology of approaches to divine violence and Christian Horfreiter’s propositions of Christian faith. The third part contains a Christian response to the flood narrative that I formulated by considering the tension between the theological imagination of Christianity and the authors of the Old Testament. Eventually, this article offers the celebration of divine violence as a response to the critics of the flood narrative.AbstrakNarasi air bah (Kej. 6:1-9:19) kerap menuai kritik dari para intelektual kontemporer akibat muatan kekerasan yang terkandung di dalamnya. Di hadapan kritik-kritik tersebut, saya mengargumenkan posisi yang memandang kekerasan dalam narasi air bah secara positif. Saya mempertahankan argumen ini melalui penjelasan bercabang tiga yang disusun dengan kajian pustaka atas tiga karya tafsir yang menyoroti kekerasan ilahi dalam narasi air bah—masing-masing dari Emanuel G. Singgih, Merilyn E. K. Clark, dan Stephen M. Wilson. Bagian pertama berisi paparan mendalam atas ketiga karya tafsir tersebut. Bagian kedua berisi analisis saya atas ketiganya dengan menggunakan tipologi pendekatan terhadap kekerasan ilahi dari Eric A. Seibert dan proposisi iman Kristen dari Christian Horfreiter. Bagian ketiga berisi sebuah respons Kristiani pada narasi air bah yang saya rumuskan dengan mempertimbangkan ketegangan antara imajinasi teologis Kekristenan dan para penulis Perjanjian Lama. Akhirnya, artikel ini menawarkan sikap merayakan kekerasan ilahi sebagai respons bagi para kritikus narasi air bah.